Knowledge, Attitudes, and Practices of Parents Facing Child and Adolescent Obesity in Brazzaville, Congo - Jean Robert Mabiala Babela MD; Evrard Romaric Nika MD; Kadidja Grâce Cléona Nkounkou Milandou MO; Steve Vassili Missambou Mandilou MD; Succes Brege Albert Bouangui Bazolana MO; Henri Germain Monabeka MD; Georges Moyen MD (SAGE Publishing, 2016)
The study aimed to assess obesity-related knowledge, attitudes, and practices of parents when facing child and adolescent obesity in order to improve the quality of care. A case-control study was conducted from February 1 to July 1, 2013. The study compared parents of obese school children (group 1 or cases; n = 254) and those school children without obesity (group 2 or controls; n = 254). These children were drawn from public and private primary schools of Brazzaville (Congo). Obesity-related knowledge was satisfactory in 83.5% of the cases, attitudes were correct in 29% of the cases, and the practices good in 25.6% of the cases. The parents' obesity-related knowledge was satisfactory when the socioeconomic level of the family was high ( P < .02), the mothers' educational level greater than primary ( P < .001), and the fathers' educational level was greater than primary ( P < 10 −4 ). The same observation was obtained with obesity-related attitudes and practices of the parents when correct. This influence remained after the adaptation of fathers' educational level. In conclusion, the disease-related knowledge of parents can be considered satisfactory in the majority of the cases; however, obesity-related attitudes and practices remain incorrect in most of the cases.